The Staphylococcus Aureus Antibiotics Resistanceâ€™s pattern in Osteomyelitis Cases at Hospital in Jambi City - Lipinwati Husman; Budi Justitia; Hanina Hanina (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Osteomyelitis is still a health problem in Indonesia, due to poor hygiene, late diagnosis, patients with open fractures who seek treatment late, treats osteomyelitis is long time and quite expensive. Osteomyelitis is an inflammation of the bone that is often caused by a bacterial infection. Osteomyelitis often occurs in open fractures, infections of the feet of diabetics, or surgical treatment of closed wounds. Osteomyelitis can be caused by bacteria, fungi, or other organisms, and is idiopathic. The bacteria that most often causes osteomyelitis is the genus Staphylococcus, which is found in 75% of cases of osteomyelitis, especially Staphylococcus aureus. We wanted to know how the prevalence of osteomyelitis with S. aureus infection was and the pattern of resistance of these bacteria to antibiotics. This research was a descriptive research with laboratory experiments. The research samples were patients with osteomyelitis who had signed informed consent form, samples were taken in the form of wound swabs/bone scrapings and blood using the total sampling method since August 2022 until December 2022. Wound swabs/bone scrapings were performed bacterial culture on Mannitol Salt Agar (MSA). MSA was incubated at 37Â°C for 18 - 24 hours. The cultures were done gram staining, catalase test and coagulase test. Cultures that grown in MSA with coccus positive gram, catalase test positive and coagulase test positive then tested resistance to antibiotics (Cefoxitin/FOX 30 mg, Ceftriaxone/CRO 30 mg, Gentamicin/CN 10 mg, Chloramphenicol/C 30 mg, and Ciprofloxacin/CIP 5 mg) using the disc diffusion method on Mueller Hinton Agar (MHA) with fresh culture bacteria 0.5 mc Farland. There are 18 samples swabs from wound, and 10 samples are identified as Staphylococcus sp. There are 9 samples that gram staining with coccus positive gram, Catalase positive test, and coagulase positive test. From 9 samples which done antibiotic sensitivity test, there are 2 samples, 3 samples, 1 sample, 3 samples, and 5 samples resistence to cefoxitin (Methicillin resistance Staphyloccus aureus/MRSA), Ceftriaxon, Chlromphenicol, Gentamisin and Ciprofloxacin respectively. There are Fifty percents of osteomyelitis samples are staphylococcal infection with 22.22 percents infection of MRSA.